The use of marginal oscillator detector with increased conversion linearity for recording broadband multiplet nuclear quadrupole resonance spectra - Samila, Andriy (Sumy State University, 2021)
This paper describes the features of choosing the sweep method and mode in the study of broadband multiplet nuclear quadrupole resonance (NQR) spectra using marginal oscillator sensor with increased conversion linearity. In particular, the work of the improved sensor in the frequency sweep mode is consid-ered when using: bipolar frequency modulation with synchronous second harmonic detection; Zeeman modulation with synchronous first harmonic detection, provided that the modulation depth is much greater than the line width; Zeeman modulation with synchronous second harmonic detection. Much atten-tion is paid to experimental studies of the NQR spectra and the orientation dependence of the relative in-tegral intensity of their resonance lines for three multiplet groups in the frequency range 20.4 MHz – 20.7 MHz of the 3/2 ↔ 5/2 115In quadrupole junction in a semiconductor layered InSe compound grown by the Bridgeman method. It is established that to obtain the optimal signal amplitude, the shape of the modulating field must be square-rectangular. The performed NQR studies in InSe confirm the complexity of the problem of polymorphism in layered crystals, which requires further research using various experi-mental techniques.
Keywords: NQR; sensors; modulation; layered semiconductors; multiplet spectra